Scattering of low-energy Ne+ ions from the stepped surface of InGaP(001)<110> at the small angles of incidence - Kutliev, U.O.; Otabaev, M.U.; Karimov, M.K.; Masharipov, F.K.; Woiciechowski, I. (Physics and Chemistry of Solid State, 2023)
Scattering of Ne+ ions at small angles of incidence from a stepped InGaP(001) <110> surface by the E0=5 keV was simulated using computer simulation. The trajectories of dechanneled ions from defect surface, as well as their energies at the scattering and scattering angle, are studied. It is shown that before dechanneling, the frequency and amplitude of the trajectory of ions, which move the surface channel formed by the stepped atom, increase. The energy distributions of these ions are obtained and the part of the spectrum corresponding to these ions is determined. It has been established that the energetic dechanneled ions formed low intensity peaks on the low-energy part of the spectrum.